Neuro control – using neuro monitoring data to control networked active instruments - Dietz Christian; Pfeiffer Jonas H.; Dingler Max E.; Lüth Tim C. (Current Directions in Biomedical Engineering, 2017)
Intraoperative neurophysiological monitoring (IONM) can be used to monitor the neural integrity and help the surgeon to reduce iatrogenic patient damage. We present a networked digital assistance system based on real-time IONM data. The system automatically reduces the power of active medical ablation instruments when they endanger neural structures. We integrated a nerve monitor into a real-time network of medical devices. In doing so, neurophysiological signals are available to all connected medical devices in real-time. With the IONM data a so-called function module Neuro Control calculates and controls the maximum allowed power for active instruments like an ultrasonic dissector.